Clinical Course and Management of Placenta Accreta Spectrum: A Case Report from Al-Zawia Central Hospital - Hwisa, Karima; Nawal Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
Placenta accreta spectrum (PAS) is a range of abnormal placental–myometrial attachments where the placenta invades or adheres to the uterine wall, typically including placenta accreta, increta, and percreta, and posing risk of severe hemorrhage and obstetric complications. “M.A.”, a 34-year-old with painless vaginal bleeding and prior cesareans, was evaluated for PAS with placenta previa and scar. Imaging confirmed PAS on the percreta end of the spectrum (central previa, anterior wall/scar invasion). A multidisciplinary team performed a cesarean birth with regional anesthesia, placental delivery, arterial ligation, and layered closure to minimize blood loss. Uneventful recovery; discharged after 3 days with postnatal follow-up and family planning counseling. This study examines the clinical features, diagnostic methods, and management strategies of placenta accreta, a serious obstetric condition characterized by abnormal placental attachment to the uterine wall. Through the follow-up, treatment, and management of this condition, the research highlights the importance of early diagnosis using imaging techniques to reduce maternal morbidity and mortality. The findings aim to support clinical decision-making and improve maternal safety in high-risk pregnancies.